Enhancement of photocatalytic efficiency of copper oxide/zinc oxide-montmorillonite photocatalyst under visible light irradiation - Chomponoot Suppaso; Nipaporn Pongkan; Sonchai Intachai; Wachiraya Rattanawongsa; Areebhorn Baoulan; Yusuke Yamauchi; Yusuke Asakura; Nithima Khaorapapong (Science and Technology of Advanced Materials)
The formation of copper oxide and zinc oxide mixture in montmorillonite was conducted by the reaction of an aqueous dispersion of Cu2+/Zn2+ exchanged montmorillonite and an aqueous solution of sodium hydroxide under hydrothermal treatment. The resulting product was characterized by X-ray diffraction, scanning and transmittance electron microscopies, as well as UV-visible and photoluminescence spectroscopies. The diffuse reflectance absorption spectra showed the absorption onsets due to copper oxide (885 nm) and zinc oxide (310 and 580 nm) in the product. The adsorption of methylene blue was fitted well by the Langmuir model with the maximum adsorption capacity of 454 mg⋅g−1. The thermodynamic studies revealed that the process is exothermic and spontaneous. The photocatalytic activity of the hybrid was assessed by the degradation of methylene blue in aqueous solution under visible light irradiation. The most active species in the photocatalytic process was hydroxyl radicals. The regenerated copper oxide/zinc oxide-montmorillonite was reused up to 5 cycles, the photodegradation efficiency dropped only 5% (from 94% to 89%), supporting the good stability of the photocatalyst. The result was in agreement with the advantages of the nanocomposite heterostructure and the unique nature of montmorillonite.